A closer look at the resection margins of buccal mucosa cancer: Their influence on local recurrence free survival. Issue 4 (24th February 2023) - Adriaansens, Carleen M. E. M.; Noorlag, Rob; Visscher, Wouter P.; de Bree, Remco; Breimer, Gerben E.; van Es, Robert J. J.
Abstract: Background: The adequate surgical margin for local control of buccal mucosa squamous cell carcinoma (BMSCC) is under debate. This study investigates surgical margins and other factors associated with local recurrence free survival (LRFS) in a large cohort of BMSCC patients. Methods: Multiple factors were evaluated retrospectively in 97 patients with BMSCC. Cox‐regression and Kaplan–Meier curves were used for analysis. Results: The local recurrence rate was 23%. The tumor‐free margin was <5.0 mm in 89% of the patients and the deep margin was significantly more often inadequate. Multivariate analysis associated pT3‐classification, former smokers, tumor‐free margin status, and postoperative (chemo)radiation (PO(ch)RT) with local recurrence. Re‐resections did not improve LRFS in patients with <5.0 mm tumor‐free margins. Conclusions: Adequate tumor‐free margins are pivotal for LRFS of BMSCC. PO(ch)RT, not re‐resection, can improve LRFS in patients with <5.0 mm tumor‐free margins.